Nur Movement di Turki dan Kesinambungan Dakwahnya Sehingga Kini - Mohd Zin, Ab Aziz; Mohd Sairi, Faridah (Jurnal Usuluddin, 2009)
This article highlights the history of the establishment of Nur Movement in Turkey by Bediuzzaman Said Nursi. The movement has played an important role in spreading Islam and to strengthen the understanding of Islam in Turkish society. However, the Nur Movement has now grown throughout the world. Collections of Nursi’s works, Rasa’il al-Nur become as main references for Nursi’s students called Tullab al-Nur. After the death of Nursi, the Nur Movement facing a number of issues led to the breakup of the group. However, despite the split, there is a wisdom that paved the way for greater development of Islamic da`wah by the movement. That is the main idea of trying to put forward in this article, the continuation of da`wah by the Nur Movement until now.